Letter - Lightfoot, R. H.
034-0150-001 Transport and General Workers' Union General Secretary: Ernest Bevin Financial Secretary: Stanley Hirst Asst. General Secretary: Arthur Deakin Telegraphic Address: "TRANSUNION SOWEST LONDON" Telephone No.: VICTORIA 7671/5 Registered Office: TRANSPORT HOUSE, SMITH SQUARE, WESTMINSTER, S.W.1 Secretary's Address 1 West Wynford St Weaste 6 9 1938 pc ack 7/9/38 TUC Delegates Dear Sirs & Bros The Check Clerks Branch passed a resolution last night 5/9/39 to ask the Delegates of the T.U.C. Conference to give their whole hearted support to the letter from Sam. Wild Commander British Battalion International Brigade Yours Respectfully R H Lightfoot 292/946/34/150